ISLAMIZATION OF KNOWLEDGE - Fakhruddin Azmi, Mely Nadia (PENDALAS: Jurnal Penelitian Tindakan Kelas dan Pengabdian Masyarakat, 2022)
Abstract The purpose of this discussion is to add insight and understanding about the Islamization of science, which means Islamizing or purifying Western product science, which has been developed and used as a reference in the discourse of creating an Islamic education system to obtain science with an "Islamic characteristic". The method in this journal is to use a literature review. The Literature Review is a description of the theory, findings and other research materials obtained from reference materials to be used as the basis for research activities to develop a clear frame of mind from the formulation of the problem to be studied. Islamic science must include faith, goodness and human justice, both individually and socially. Means science is based on religion with the aim of human benefit. The Islamization of science aims to realize the progress of Islamic civilization. Each one also does not want the condition of Muslims to deteriorate while accelerating the development of science and technology progress. With the efforts of the Islamization of the science movement, it is hoped that the scientific dichotomy between religious science and modern science can be integrated and given integrally in the educational process. Science can be a medium in achieving a better life.